Post-PCI outcomes in STEMI patients with coronary ectasia: meta-analysis. (3rd April 2021) - Mir, Tanveer; Sattar, Yasar; Uddin, Mohammed; Changal, Khalid Hamid; Kumar, Kartik; Attique, Hassan Bin; Kabashneh, Sohaip; Ullah, Waqas; Lohia, Prateek; Alraies, M Chadi; Blank, Nimrod; Afonso, Luis; et al.
ABSTRACT: Background: Coronary ectasia (CE) is defined as dilation of the coronary artery, 1.5 times that of the surrounding vessel. Outcomes of percutaneous intervention (PCI) in patients with CE presenting as ST-elevated myocardial infarction (STEMI) remain a topic of debate. Methods: Studies comparing outcomes of PCI in CE versus no-ectasia (NE) STEMI patients were identified. Baseline angiographic characteristics include thrombolysis in myocardial infarction (TIMI) 0–1 flow, right coronary artery (RCA) involvement, and primary outcomes including thrombus aspiration, no-reflow, mortality, and TIMI-3 post-PCI. Odds ratio (OR) and 95% confidence interval (CI) were calculated. Results: Six studies (n = 5746, CE-340 and NE-5406) qualified for the analysis. RCA involvement was more common in CE than NE, OR-1.39 (95%CI1.06–1.82, p-0.02). Pre-procedure TIMI-0-1 was of comparable results between the groups (p-1.13). Higher thrombus aspiration for CE (OR 2.18, 95%CI1.44–3.32;p-<0.001). CE had higher incidence of no-reflow (OR 4.07, 95%CI2.42–6.84;p-<0.001). TIMI-3 flow post-PCI was achieved less commonly in the CE group (OR-0.64, 95%CI-0.48–0.86;p-<0.001). Mortality on follow-up was comparable (0.83, 95%CI0.39–1.78;p-0.63). Metaregression analysis did not show confounding effects from comorbidities. Conclusion: Coronary ectasia patients with STEMI had higher rates of PCI failure and no-reflow than NE; however, mortality during follow-up was comparable.